Entrepreneurship intention UiTM Malacca City Campus students / Nur Idayu Mad Zam and Nur Wahida Jamion - Mad Zam, Nur Idayu; Jamion, Nur Wahida (Faculty of Business and Management, 2014)
Research on entrepreneurship intention has and continues to be interest due to the importance to the development for many countries. There is various issue and many factors that influence entrepreneurship intention. Nowdays, students were competed among themselves in order to be employed. As there is a lot of graduate from different university and different background, they should consider an entrepreneur as an alternate career for them. This study examines entrepreneurship intention among UiTM Malacca City Campus students. Using a questionnaire survey on part 5 students Faculty of Business Management UiTM Malacca City Campus. The questionnaire have being distributed to 201 students from 6 courses of Faculty of Business Management which is Human Resources, Finance, International Business, Office Management and Insurance. This study examines whether part 5 students have an intention to start-up their own business. It also examines whether interest, resources and social networking influence the students to become an entrepreneur. The results show that all the factors examine play an important role in encouraging the students to become an entrepreneur. At the end of this research, some of the recommendation are also having been discussed.